Planning TOD with land use and transport integration: a review - Herika Muhamad Taki; Mohamed Mahmoud H. Maatouk; Emad Mohammad Qurnfulah; Mohammed Omayer Aljoufie (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Transit Oriented Development (TOD) implementation in urban development is globally adopted by many countries in the world in a rapid manner. However, the city and regional acute problems is still propagating. An in-depth study to examine this problem is required. Thus, this paper review various study related to the integration of land use and transport with TOD. The subject of the paper will be described as follow: Method, criteria and indicators of TOD'S research, Reviewing the strategic plan and the public transport plan in the worldwide, and Cross-continent comparison of integration planning. In conclusion, practice and integration of TOD through land use and transportation is an alternative solution in acquiring the objective of the master plan and to solve urban issues such as urban congestion, reduce travel time, and car dependency.